Genomic Characterization of Pseudorabies Virus Strains Isolated in Italy. Issue 4 (18th January 2013) - Sozzi, E.; Moreno, A.; Lelli, D.; Cinotti, S.; Alborali, G. L.; Nigrelli, A.; Luppi, A.; Bresaola, M.; Catella, A.; Cordioli, P.
Summary In this study, we undertook the genomic characterization of 54 pseudorabies virus (PRV) strains isolated in Italy during 1984–2010. The characterization was based on partial sequencing of the UL44 (gC) and US8 (gE) genes; 44 strains (38 for gene gE and 36 for gC) were isolated on pig farms; 9 originated from dogs and 1 from cattle. These porcine PRV strains, which were closely related to those isolated in Europe and America in the last 20 years, and the bovine strain bovine/It/2441/1992 belong to cluster B in both phylogenetic trees. Six porcine strains that do not belong to cluster B are related in both gE and gC phylogenetic trees to the 'old' porcine PRV strains isolated in the 1970s and 1980s. In the last two decades, the presence of these strains in domestic pig populations has been reduced drastically, whereas they are prevalent in wild boar. The two remaining strains have an interesting genomic profile, characterized by the gC gene being closely related to the old porcine PRV strains, and the gE gene being similar to that of recently isolated strains. Three strains originating from working dogs on pig farms are located in cluster B in both phylogenetic trees. Five strains isolated from hunting dogs have a high degree of correlation with PRV strains circulating in wild boar. The last isolate has a gC gene similar to that in the two porcine strains mentioned previously, and the gE gene is correlated with the strains isolated from hunting dogs. These results provide interesting insight into the genomic characterization of PRV strains and reveal a clear differentiation between the strains isolated from hunting dogs that are related to the wild boar strains and those originating from domestic pigs.